Composite facing of peg shaped lateral incisor- a case report. - Sultana, Asma; Karim, Fahd AA; Quader, SM Abdul; Tasnim, Tarannum; Hossain, Mahabubul; Nasrin, Kazi Farah (Update Dental College Journal, 2017)
In appearance related society that we live in , the younger adolescent patient caneasily become self conscious if their teeth are different to others. A common from of microdontia which affect the maxillary lateral incisor is known as peg lateral. Treatment approach has to be case specific and depends on the condition of primary predecessor, number of missing teeth, status of occlusion and patient preference.This clinical report describes the treatment of both sided peg-shaped lateral incisors that were restored with resin composite laminate veneers. The aim of the treatment is to close the diastema and restore the contours of the tooth. These simple procedures may be a cost effective treatment alternative to restore the esthetics of these teeth and may prove particularly growing patients before more definitive restorations can be considered. Update Dent. Coll. j: 2016; 6 (2): 31-33